1999
DOI: 10.1176/ajp.156.6.816
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Sexual Abuse as a Risk Factor for Depression in Women: Psychosocial and Neurobiological Correlates

Abstract: Childhood sexual abuse is an important early stressor that may predispose individuals to adult-onset depression by means of dysregulation of the HPA axis. Investigation of the mechanisms mediating the relationship between childhood sexual abuse and adult-onset depression, and the study of gender differences in exposure to this and other stressors, may improve our understanding of the etiology of depressive illness in general.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
254
2
24

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 436 publications
(301 citation statements)
references
References 90 publications
18
254
2
24
Order By: Relevance
“…In conclusion this study has shown significant stress-system alterations in relation to some adverse life events. It seems as childhood sexual abuse and feelings of neglect are related to long-term psychobiological effects, and may also be behind depressive and/or anxiety illness during adulthood [39] reflecting an allostatic load. Fig .…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion this study has shown significant stress-system alterations in relation to some adverse life events. It seems as childhood sexual abuse and feelings of neglect are related to long-term psychobiological effects, and may also be behind depressive and/or anxiety illness during adulthood [39] reflecting an allostatic load. Fig .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, women are more likely to develop major depression after ELS than men (Weiss et al, 1999). There is also recent evidence that genetic variations moderate the effects of ELS on depression (Caspi et al, 2003).…”
Section: Evidence For a Role Of Els In The Pathophysiology Of Depressmentioning
confidence: 99%
“…Such confounding may also occur in studies of risk factors for depression. For example, the observed preponderance of women in depression might be due to gender differences in ELS or the response to it (Weiss et al, 1999). Also, symptom patterns of depression as well as comorbidity rates between depression and other disorders, such as substance abuse, might be a function of ELS (Molnar et al, 2001).…”
Section: Evidence For Differences In the Neurobiology Of Depression Dmentioning
confidence: 99%
“…Sex differences in exposure and response to stress may also affect SV. Women are more likely than men to develop depression following a stressful life event early in life 300 and their HPA axis is more susceptible to PS-induced programming. [301][302][303] Women have a lower mean rate of 5-HT synthesis compared to men, while men and women appear to have similar stores of brain 5-HT.…”
Section: Biopsychological Interactionsmentioning
confidence: 99%
“…313 Furthermore, the female HPA axis may be more reactive to stress, possibly due to sex hormones. 300 In terms of coping styles, women have been reported to use more emotion-focused coping than men, while men more often use rational and problem-focused coping. 305 Women appear to be more likely than men to respond to stress with rumination -focusing inward on feelings of distress and personal concerns rather than taking action to relieve their distress.…”
Section: Biopsychological Interactionsmentioning
confidence: 99%